Coexistence of nail lichen planus and lichen planus pigmentosus - Lemes, Luciana Rodino (An Bras Dermatol, 2016)
We describe a fifty-six-year old, Afro-descendent female patient showing dystrophy of her twenty nails and hyperchromic, asymptomatic macule on her face. Histopathological examination of the macule showed vacuolization of the basal layer, melanophages in the superficial dermis and lymphoplasmocytic inflammatory infiltrate. Nail biopsy revealed orthokeratotic hyperkeratosis and lichenoid inflammatory infiltrate. Lichen planus pigmentosus is an uncommon variety of lichen planus. It is characterized by typical hyperpigmented macules on the face and neck. Nail changes might be present in 10% of lichen planus cases, but no associations with lichen planus pigmentosus have been described. We report a case of lichen planus in twenty nails associated with lichen planus pigmentosus on the patient's face.